1997
DOI: 10.1111/j.1349-7006.1997.tb00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations of the MEN1 Gene in Japanese Kindred with Multiple Endocrine Neoplasia Type 1

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an autosotnal dominant familial cancer syndrome. The responsible gene MEN1 has recently been isolated, and its germline mutations have been identified in affected individuals in the United States, Canada and Europe. We screened for MEN1 mutations by direct nucleotide sequencing of all protein‐coding regions, and identified five distinct germline mutations in five among six Japanese kindreds with familial MEN1 or familial hyperparathyroidism. The mutations were disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 13 publications
3
39
1
Order By: Relevance
“…This was contradictory to the previous report showing that no mutation of the MEN1 gene was detected in 5 probands with FHP in the United States and Canada [10]. On the other hand, it has recently been reported that a Japanese patient with FHP had a germline mutation of the MEN1 gene (Y353X in exon 8), although the clinical evaluation for MEN1 was not described in this family [13]. Primary hyperparathyroidism is usually expressed at an early age (85% by age 35) and has a high penetrance (95%) in MEN1 [14].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This was contradictory to the previous report showing that no mutation of the MEN1 gene was detected in 5 probands with FHP in the United States and Canada [10]. On the other hand, it has recently been reported that a Japanese patient with FHP had a germline mutation of the MEN1 gene (Y353X in exon 8), although the clinical evaluation for MEN1 was not described in this family [13]. Primary hyperparathyroidism is usually expressed at an early age (85% by age 35) and has a high penetrance (95%) in MEN1 [14].…”
Section: Discussioncontrasting
confidence: 54%
“…The deletion in exon 9 found in our patient predicts the loss of the C-terminal portion of menin. The loss of this portion may be important in the pathogenesis of parathyroid gland hyperplasia, because nine types of mutation in exon 9 have also been reported in MEN1 patients [10,11,13,18]. Very recently, Guru et al [19] have reported that menin is a nuclear protein which has at least 2 independent nuclear localization signals in the C-terminal portion.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from leukocytes was extracted and the coding exons and exon-intron boundaries of the MEN1 gene (NM_003977.2) were PCR-amplified and screened by direct sequencing. 8 Moreover, sequencing of the SDHA, SDHAF2, SDHB, SDHC, and SDHD genes (NM_004168.2, NM-017841.1, NM_003000.2, NM_003001.3, NM_003002.2), TMEM127 (NM_017849.1), MAX (NM_002382.3) and CDKN1B gene (NM_004064) were performed on the proband's DNA. The potential effect of the missense variant on menin protein was evaluated in silico using a battery of tools: Polyphen2 (http//:www.genetics.bwh.harvard.edu), UMD predictor, 9 and Alamut 2.2.0 software (Interactive Biosoftware, Rouen, France).…”
Section: Sequencing Analysis Of Genomic Dnamentioning
confidence: 99%
“…Although the physiological role of the protein remains under investigation, it has been speculated to suppress tumorigenesis. Recently various heterozygous germline mutations in the MEN1 gene have been identified in cases of MEN1 (10)(11)(12)(13). Here, we report a family with MEN1 whoshowed a mutation of lOOldelC in the proband and his son.…”
Section: Introductionmentioning
confidence: 84%
“…Informed consent was obtained for genetic analysis of the family, and the proband and his two children (a son and a daughter) agreed to be examined. Osaka) and PCR buffer (Takara Shuzo Co.) (10). The initial denaturation was performed for 1 min at 95°C and was followed by 30 cycles of denaturation at 95°C (1 min), annealing at 64-68°C (2 min) and extension at 72°C (1 min) (10 vyVk/w Results Germline mutation analysis PCR amplification and direct sequencing of genomic DNA extracted from the blood of the proband and his son showed a heterozygous germline deletion of cytosine at position bp 1001 in exon 6 of the MEN1 gene (Fig.…”
Section: Case Reportmentioning
confidence: 99%